The effect of PAMAM dendrimers with amine or hydroxyl terminal groups on the bioadhesive properties of hydrogels with clotrimazole - Sosnowska, K.; Szekalska, M.; Winnicka, K. (Polimery, 2021)
Polyamidoamine dendrimers (PAMAM) belong to a relatively new class of polymers that are evaluated as efficient systems for drug delivery due to their nanosize range, ability to improve solubility, permeability and pharmacological activity of many drugs. In this study, the influence of PAMAM dendrimers of generation2 (G2) and 3 (G3) with -NH2or -OH terminal groups (PAMAM-NH2 and PAMAM-OH, respectively) on the bioadhesive properties, viscosity and yield stress of polyacrylic acid polymer hydrogels with clotrimazole was investigated. We show that the addition of PAMAM-NH2 dendrimers G2 and G3 into the hydrogel structures caused, in both cases, an about 2-fold decrease in viscosity of the hydrogels and a 1.3 and 1.4-fold decrease in the value of yield stress, respectively. We also found that PAMAM dendrimers with -NH2 terminal groups induced the highest decrease in the work of adhesion between hydrogels and the examined adhesive layers.